How Does it Feel to be a Teacher? Personal Journeys and Lessons for a Malaysian University - Hazadiah Mohamad Dahan; Siti Salina Ghazali (UiTM Publisher, 2007)
This paper is an attempt to understand beginning teachers' perceptions of their profession after an eight to ten-week stint of teaching in schools. Beginning teachers of the Faculty of Education at Universiti Teknologi MARA (UiTM), Malaysia, were asked to respond in writing to the simple question: How does it feel to be a teacher? Using a qualitative approach the data were analysed for insights into the challenges they faced as beginning teachers, their hopes, beliefs and anguish; the understandings they gleaned from training and their interpretation and presentation of these understandings during their interactions with students. The paper explores and describes the beginning teachers' perceptions of being teachers, the impact of their teaching stints on their perceptions, and the factors they have identified as inhibiting or enhancing their potential as teachers. The paper concludes by discussing ways and means of facilitating their growth into maturity as competent teachers. It focuses on how to ensure the retention of beginning teachers in the profession, the kind of programme required to make them adjust to the culture of teaching as new members of a community of practice, and the kind of support they would require in order to develop their pedagogical skills.